Effects of extrusion on ileal and total tract digestibility of nutrients and energy in soybean for weanling pigs - Milani, Natália Cristina; Paula, Vinicius Ricardo Cambito de; Azevedo, Cândida Pollyanna Francisco; Sedano, Anderson Aparecido; Scarpim, Lucas Bassi [UNESP]; Moreira Junior, Hélio; Duarte, Dave Hanneman Alves; Carciofi, Aulus Cavalieri [UNESP]; Trindade Neto, Messias Alves da; Ruiz, Urbano dos Santos (Elsevier, 2022)
This study evaluated the ileal and total tract digestibility of nutrients and energy in soybean extruded at three different conditions, compared to deactivated soybean (DS), in newly weaned piglets. Forty crossbred barrows (28 d old and 7.64 ± 0.88 kg body weight) were allotted to 5 dietary treatments with 8 replications per treatment. The diets consisted of an N-free diet, to determine endogenous losses of amino acids (AA), and 4 diets containing 30% of test ingredients as the only source of protein and AA: soybean extruded at 82 °C (SB82), 122 °C (SB122) and 137 °C (SB137), and DS, which was used as a control. The DS was produced by heating the whole raw soybean, from 63 °C to 107 °C under pressure. Titanium dioxide was added to the diets as an indigestible marker. After a 5 d adaptation period, partial feces collection was performed over 5 d and samples of ileal digesta were collected after piglets euthanasia. The apparent total tract digestibility of dry matter, gross energy (GE), crude protein (CP), neutral detergent fiber and acid detergent fiber, and apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of CP and AA were evaluated. Analysis of variance was performed and the means compared by Tukey test when P < 0.05. The extrusion of soybean at 122 °C and 137 °C was effective in reducing trypsin inhibitors content, and promoted adequate nutrient and energy digestibility of soybean in piglets. These effects could be observed as the AID of Lys and Trp, and SID of Lys of SB122 and SB137 were greater (P < 0.05) than those of SB82 and DS. The AID and SID of CP and remaining AA were similar among SB122, SB137 and DS, but greater (P < 0.05) than those of SB82. In addition, the ATTD of GE of SB122 was 3–4% greater (P < 0.05) than those of DS and SB82, showing an important effect of extrusion on energy use by pigs. Thus, extrusion of soybean at 122 °C is recommended and SB122 is a feed ingredient with greater nutritional value than DS or SB82 for young pigs.
Keywords: Anti-nutritional factor; Feed processing; Trypsin inhibitor